Effect of Doped Nickel on the Structural and Electrical Properties of Alumina Prepared by the Chemical Co-precipitation Method - Omer H. Abas (Journal of Global Pharma Technology, 2016)
Pure α-Al2O3 compound and its nickel (Ni) composites were prepared with different weight ratios according to the formula ((NiO) x (Al2O3)1-x), where (x = 0, 0.125, 0.25, 0.375, 0.50 g) through the chemical co-precipitation method. These were calcined at 1300 ͦC, and the prepared samples were characterized using different techniques such as XRD and FT-IR spectroscopy. The investigation by X-ray diffraction (XRD) showed that the prepared α-Al2O3had only one pure phase of α-Al2O3 with a crystallite size of 33nm, while the NiAl2O4 composites were formed in different phases according to the weight ratios of the NiO used (NiO/NiAl2O4, NiAl2O4, Al2O3 / NiAl2O4). In addition, the crystallite sizes of the phases of the resulting composites ranged from 35 – 50nm, and increased with increasing NiO content. The best result was obtained for the NiAl2O4 composite at x = 0.25g, where the characterization by FT-IR spectroscopy showed that the pre-calcined composites at 500 ̊C initially formed the spinal phase of the doped composites, but the composites prepared at the final sintering temperature of 1300 ͦC formed the pure and spinal phases. The effective NiO4group was formed at the tetragonal sites and a part of it was formed in the octahedral sites, while the effective group (AlO6) was formed at the octahedral sites, thereby indicating that the material was in the spinal inverse and spinal phases. The A.C. conductivity indicated that the highest value of the dielectric constant was at a minimum frequency and decreased with increasing frequency at low frequencies as a result of the effect of a vacuum charge and ionic polarizations. However, at high frequencies, it was found that the dielectric constant did not depend on the frequency, thereby indicating that the dipole moments followed the electric field only at low frequencies. In addition, the A.C. conductivity showed that the conductivity increased with increases in the frequency according to the correlated barrier hopping model (CBH), where the charge carriers jump up from one site to another causing the A.C. conductivity to increase with increasing frequencyKey terms: Nickel Alumina, Alumina, Dielectric, Precipitation method.